Dihydromyricetin Reverses Thioacetamide-Induced Liver Fibrosis Through Inhibiting NF-κB-Mediated Inflammation and TGF-β1-Regulated of PI3K/Akt Signaling Pathway - Zhao, Yingchun; Liu, Xinglong; Ding, Chuanbo; Gu, Yan; Liu, Wencong (Frontiers in Pharmacology, 2021)
As a natural active substance, dihydromyricetin (DHM) has been proven to have good hepatoprotective activity. However, the therapeutic effect of DHM on liver fibrosis has not been studied, which has become a liver disease threatening the health of people around the world. The purpose of this study was to investigate the effect of DHM as a new nutritional supplement on thioacetamide (TAA)-induced liver fibrosis. The liver fibrosis model was established by intraperitoneal injection of TAA (200 mg/kg) for 8 weeks, and oral administration of DHM (20 mg/kg and 40 mg/kg) after 4 weeks of TAA-induced. The results showed that DHM treatment significantly inhibited the activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in serum of liver fibrosis mice, and increased the levels of superoxide dismutase (SOD) and glutathione (GSH) while reversed the level of MDA. In addition, histopathological examination illustrated that TAA induced the inflammatory infiltration, apoptosis and fibroatherosclerotic deposition in liver, which was further confirmed by western-blot and immunofluorescence staining. Moreover, DHM inhibited hepatocyte apoptosis by regulating the phosphorylation level of phosphatidylinositol 3-kinase (PI3K), protein kinase-B (AKT) and its downstream apoptotic protein family. Interestingly, immunofluorescence staining showed that DHM treatment significantly inhibited a-SMA, which was a marker of hepatic stellate cell activation, and regulated the expression of transforming growth factor (TGF-β1). Importantly, supplementation with DHM significantly inhibited the release of NF-κB signaling pathway and pro-inflammatory factors in liver tissue induced by TAA, and improved liver fiber diseases, such as TNF-α and IL-1β. In conclusion, the evidence of this study revealed that DHM is a potential hepatoprotective and health factor, and which also provides the possibility for the treatment of liver fibrosis.